Acceptability of the Nestorone®/Ethinyl Estradiol Contraceptive Vaginal Ring: Development of a Model; Implications for Introduction - Merkatz, Ruth B. (Contraception, 2014)
OBJECTIVES: Develop and test a theoretical acceptability model for the Nestorone®/ethinyl estradiol (NES/EE) contraceptive vaginal ring (CVR); explore whether domains of use within the model predict satisfaction, method adherence and CVR continuation. STUDY DESIGN: Four domains of use were considered relative to outcome markers of acceptability, i.e. method satisfaction, adherence, and continuation. A questionnaire to evaluate subjects’ experiences relative to the domains, their satisfaction (Likert scale), and adherence to instructions for use was developed and administered to 1036 women enrolled in a 13-cycle Phase 3 trial. Method continuation was documented from the trial database. Stepwise logistic regression (LR) analysis was conducted and odds ratios calculated to assess associations of satisfaction with questions from the 4 domains. Fisher’s exact test was used to determine the association of satisfaction with outcome measures. RESULTS: A final acceptability model was developed based on the following determinants of CVR satisfaction: ease of use, side effects, expulsions/feeling the CVR, and sexual activity including physical effects during intercourse. Satisfaction was high (89%) and related to higher method adherence [OR 2.6(1.3,5.2)] and continuation [OR5.5(3.5, 8.4)]. According to the LR analysis, attributes of CVR use representing items from the 4 domains — finding it easy to remove, not complaining of side effects, not feeling the CVR while wearing it, and experiencing no change or an increase in sexual pleasure and/or frequency — were associated with higher odds of satisfaction. CONCLUSION: Hypothesized domains of CVR use were related to satisfaction, which was associated with adherence and continuation. Results provide a scientific basis for introduction and future research.